Joint Decision Making for Production and Marketing - Ulusoy, Gündüz; AKTİN, AYŞE TÜLİN (My University, 1995)
The prosperity of a firm depends highly on the functional integration of its various departments, and in particular the cooperation between the production and the marketing departments appears to have a large impact on the well-being of a firm. The aim of this study is to model an aggregate production planning problem that considers the production and marketing functions in a simultaneous manner. The developed multi-period, multi-product model with the objective of profit maximization reflects the characteristics of both departments. Demand for each product in each period is generated through the use of demand functions. The advertising efficiency and price of the products are determined within the model. The cash outflow for advertising expenditures is approximated by a quadratic cost function, and the production cost exhibits economies of scale. Also, stockouts are taken into consideration in the form of backlogging. A solution methodology consisting of two phases is developed, and cases displaying some important characteristics are generated and solved in order to test the performance of the proposed model. This methodology incorporates linear mixed integer programming which is embedded in two different search techniques, along with a dynamic programming-based heuristic procedure.